The Relationship Between Workload and Stress Levels Of Nurses At Uptd Puskesmas Benteng Selayar Islands Regency (Comprehensive Health Care, 2024)
Background : Workload in the room is not always a cause of stress for nurses, workload will be a source of stress if the amount of workload is not proportional to the nurse's physical, psychological, and skill abilities as well as available time. A survey conducted by the Health and Safety Executive (HSE) stated that work-related stress and depression in 2017/2018 was 595,000 cases with a prevalence rate of 1,800 per 100,000 workers. Work-related stress and depression also contribute 44% of all cases of work-related health disorders and 57% of sick absences from the office (HSE, 2022).Objective: The purpose of this study is to find out the relationship between workload and stress levels of nurses at the UPTD Benteng Health Center, Selayar Islands Regency in 2023.Research Method: The research method used is a type of observational analytical quantitative research with a cross- sectional approach. The data analysis used in this study is Chi-Square (Fisher's Exact Test).Research Sample: The number of samples in this study is 35 nurses.Research Results: There is a relationship between workload and the level of stress of nurses at the UPTD Benteng Health Center, Selayar Islands Regency in 2023 with a p value of 0.000.Conclusion: The workload and stress level of nurses at the UPTD Benteng Health Center, Selayar Islands Regency are mostly in the medium category. there is a relationship between Workload and Stress Levels of nurses at the UPTD Benteng Health Center, Selayar Islands Regency in 2023.